A cyclic austenite reversion treatment for stabilizing austenite in the medium manganese steels. (15th July 2017) - Zhu, Jianing; Ding, Ran; He, Jianguo; Yang, Zhigang; Zhang, Chi; Chen, Hao
Abstract: Tailoring the fraction and stability of retained austenite in the medium manganese steel has always been an issue of great industrial interest. A novel cyclic austenite reversion treatment (ART) is proposed to obtain considerable amount of retained austenite in a Fe-0.21C-4.53Mn (wt%) steel, and it is found to be more efficient by comparison with the conventional ART. Transformation kinetics, alloying element partitioning and microstructure evolution during the cyclic and conventional austenite reversion process is discussed. Graphical abstract: